The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.4172/2155-9880.1000146
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hyperosmotic Sodium Chloride Perfusion on Ischemia/Reperfusion Injury in Isolated Hearts of Normal and Stroke-Prone Spontaneously Hypertensive Rats

Abstract: Background: Hyperosmotic solutions have been used successfully in different shock resuscitations with cardioprotection. This study was to examine the effects of hyperosmotic sodium chloride on isolated heart function and heart responses to ischemia/reperfusion in normotensive and hypertensive rats. The roles of hyperosmolarity-induced antioxidants including hyperosmolarity-relevant heat shock proteins as well as vasodilating endothelial nitric oxide synthase (eNOS) and vasoactive catecholamines were investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…In Shen's et al [10] study, prefused with hyperosmolar NaCl gave similar results: increased coronary artery flow and decreased coronary artery resistance, increased left ventricular function, and increased levels of catalase but not SOD. Shen et al [10] also compared the effects of a 2 hour perfusion of rats hearts with solution made hyperosmolar with 4 different osmolytes (NaCl, glucose, mannitol, and raffinose) and found no significant differences in levels of the cellular constituents measured. They did not, however look at left ventricular function.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…In Shen's et al [10] study, prefused with hyperosmolar NaCl gave similar results: increased coronary artery flow and decreased coronary artery resistance, increased left ventricular function, and increased levels of catalase but not SOD. Shen et al [10] also compared the effects of a 2 hour perfusion of rats hearts with solution made hyperosmolar with 4 different osmolytes (NaCl, glucose, mannitol, and raffinose) and found no significant differences in levels of the cellular constituents measured. They did not, however look at left ventricular function.…”
Section: Discussionsupporting
confidence: 57%
“…They did not, however look at left ventricular function. Our findings and Shen's et al [10], therefore, may be due entirely to the hyperosmolarity.…”
Section: Discussionmentioning
confidence: 38%
See 1 more Smart Citation
“…Heart collects the deoxygenated blood from the body and pushes it to the lungs where it becomes oxygenated, and then heart pumps the oxygen rich blood to the body. Normal functioning of heart is very important to lead a healthy life [5]. Vasodilation is widening of blood vessels caused by relaxation of smooth muscle cells in the vessel walls particularly in the large arteries, smaller arterioles and large veins thus causing an increase in blood flow [6].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggested no association between alcohol intakes and type 2 diabetes. Systolic and diastolic heart function, myocardial creatine phosphokinase leakage and myocardial antioxidants after ischemia/ reperfusion were examined [42].…”
Section: Heavy Alcohol Consumptionmentioning
confidence: 99%